2012
DOI: 10.4028/www.scientific.net/amr.455-456.69
|View full text |Cite
|
Sign up to set email alerts
|

A Research on Separation Mechanism of Cylindrical Hydrocyclone

Abstract: Using the Fiber Quantity Analyzer (FQA) for analysis of the paper pulp fiber moving in the Cylindrical Hydrocyclone, making use of the way of Limited Element Analysis and Calculation Fluid Dynamic for the numerical simulation of the velocity distribution of moving process. Based on the mathematic model of it, point out the idea of design on the geometric parameters of the cylindrical hydrocyclone. The result show, the suit length of pole is benefit to improve the machine handle ability and separation efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Flat-bottomed hydrocyclones, which are usually implemented in closed-circuit grinding and classification systems in mineral processing, have the advantages of low concentration of underflow, low allocation of fine particles, and little plugging; however, coarse particle misplacement in overflow can occur . Lu et al combined numerical simulations and experiments to investigate the flow field pattern inside a flat-bottomed hydrocyclone, and the results showed that increasing the cylindrical height could increase the effective centrifugal settlement space, prolong the particle residence time, reduce the separation pressure drop, and improve the hydrocyclone treatment capacity. Jiang et al , investigated the separation performance of a flat-bottomed hydrocyclone with a W-type spigot, and simulation and experimental results revealed that under the guiding effect of a flat-bottomed profile and W structure, fine particles were returned to the internal swirling flow to achieve secondary separation.…”
Section: Introductionmentioning
confidence: 99%
“…Flat-bottomed hydrocyclones, which are usually implemented in closed-circuit grinding and classification systems in mineral processing, have the advantages of low concentration of underflow, low allocation of fine particles, and little plugging; however, coarse particle misplacement in overflow can occur . Lu et al combined numerical simulations and experiments to investigate the flow field pattern inside a flat-bottomed hydrocyclone, and the results showed that increasing the cylindrical height could increase the effective centrifugal settlement space, prolong the particle residence time, reduce the separation pressure drop, and improve the hydrocyclone treatment capacity. Jiang et al , investigated the separation performance of a flat-bottomed hydrocyclone with a W-type spigot, and simulation and experimental results revealed that under the guiding effect of a flat-bottomed profile and W structure, fine particles were returned to the internal swirling flow to achieve secondary separation.…”
Section: Introductionmentioning
confidence: 99%